Proyeksi Kebutuhan Energi Listrik Kabupaten Indragiri Hulu Berdasarkan Pertumbuhan Beban Menggunakan Model DKL 3.2 (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Projections are estimates of future state using the existing data at the present time. the higher rates of economic growth in a region, the need for electricity will increase as well, this condition requires the need to do a projected electricity need. This condition needs to be done that requires electrical energy demand projections. Projections done using DKL Model 3.2, this model prepared by combining several methods such as econometrics, trends and analytical sectoral approaches, namely households, businesses, the public and industry. The data used is the historical data of 8 years before the projection that the number of customers, the electrical energy consumption and economic growth. Projections made in the region of PLN Indragiri Hulu district beginning in 2015-2025, results from this study is that the number of subscribers grew by 16.63% per year, the electricity needs of 234,667.517 MWh in 2015 grew into 863,877.211 MWh in 2025, and peak load in 2015 amounted to 30.07 MW grow to be 110.68 MW in 2025. the capacity of power plants in the county capable of Indragiri Hulu 38.35 in 2015 and 48.35 MW in 2016 is only able to serve peak load until the year 2017 reached 47.85 MW. But in 2018 until 2025 the existing generation capacity is no longer sufficient to reach the peak load of 59.44 MW in 2018 and 110.68 MW in 2025.Keywords: Projection, electrical energy requirement, DKL 3.2